2018
DOI: 10.1177/2047487318802692
|View full text |Cite
|
Sign up to set email alerts
|

Masked hypertension incidence and risk factors in a prospective cohort study

Abstract: Aims Masked hypertension may affect up to 30% of the general population and is associated with a high cardiovascular disease risk. No previous study has examined the incidence of masked hypertension and its risk factors. The study aim was to determine the incidence of masked hypertension and to examine its related risk factors. Methods This is a cohort study including 1836 initially normotensive participants followed up on average for 2.9 years. Blood pressure was measured using Spacelabs 90207. Manual blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 31 publications
3
7
0
3
Order By: Relevance
“…The prevalence of white-coat hypertension remained stable with a slight trend to decline through the age groups, whereas that of masked hypertension steadily increased. The increased prevalence of masked hypertension in the elderly can be explained by the increased prevalence of nocturnal hypertension, as suggested by previous large population studies [2,4,[29][30][31]. This finding, coupled with the evidence that masked hypertension is associated with an increased risk of fatal and nonfatal cardiovascular events, with a risk profile similar to that of sustained hypertension, further supports the importance of ABPM for an improved hypertension evaluation and management [32].…”
Section: Discussionsupporting
confidence: 69%
“…The prevalence of white-coat hypertension remained stable with a slight trend to decline through the age groups, whereas that of masked hypertension steadily increased. The increased prevalence of masked hypertension in the elderly can be explained by the increased prevalence of nocturnal hypertension, as suggested by previous large population studies [2,4,[29][30][31]. This finding, coupled with the evidence that masked hypertension is associated with an increased risk of fatal and nonfatal cardiovascular events, with a risk profile similar to that of sustained hypertension, further supports the importance of ABPM for an improved hypertension evaluation and management [32].…”
Section: Discussionsupporting
confidence: 69%
“…The traditional related factors for hypertension include genetic factors and environmental factors (such as diet, mental stress and smoking, etc.). Previous studies found that age, sex, smoking history, drinking history, BMI, diabetes history and cardiovascular history of family members were related factors for MH (Wang et al, 2017;Kario et al, 2019;Trudel et al, 2019), and related factors for WCH included smoking history, alcohol consumption history, age and sex (Afsar, 2013;Omboni et al, 2016;Kario et al, 2019). In the current study, we found that smoking and family history of coronary heart disease were related factors for WCH.…”
Section: Comparison With Prior Worksupporting
confidence: 58%
“…Other studies in Africa have reported a higher prevalence of MUCH between 23% and 34.6% . Previous findings indicate that older age, male sex, increased BMI, smoking, and alcohol intake predict occurrence of masked hypertension. Risk of adverse cardiovascular events is higher in patients with MUCH compared to WUCH and controlled hypertension, also MUCH and TUCH predispose patients to similar risk of adverse cardiovascular outcomes and all‐cause mortality .…”
Section: Discussionmentioning
confidence: 91%